Aspek Klinik, Genetik dan Molekuler Osteogensis Imperfekta - Mariska Mariska; Elza Ibrahim Auerkari (Faculty of Dentistry, Universitas Indonesia, 2015)
Osteogenesis imperfects (OI) is a heritable disorder of connective tissue that mainly affects the bones. Being always associated with bone fragility, it is also known as "brittle bone" disease. Multiple bone fractures with minimal or absent trauma, dentinogenesis imperfects, short stature, blue slerae, and in adult years, hearing loss. Most cases of OI, which is inherited in an autosomal dominant manner, result from mutations affecting the genes COL1A1 (collagen type I alpha 1) and COL1A2 (collagen type I alpha 2) that encode pro-α 2 chains of type I collagen. The type I collagen molecule accounts for about 90% of the organic matrix of the bone. In addition, collagen forms a family of proteins that strengthen and support many tissues in the body, including cartilage, tendons, skin, and the white part of the eye (sclera). This paper aims to review the genetic contribution to OI.